The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1021/jm301020q
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Highly Potent, Selective, and Brain-Penetrable Leucine-Rich Repeat Kinase 2 (LRRK2) Small Molecule Inhibitors

Abstract: There is a high demand for potent, selective, and brain-penetrant small molecule inhibitors of leucine-rich repeat kinase 2 (LRRK2) to test whether inhibition of LRRK2 kinase activity is a potentially viable treatment option for Parkinson's disease patients. Herein we disclose the use of property and structure-based drug design for the optimization of highly ligand efficient aminopyrimidine lead compounds. High throughput in vivo rodent cassette pharmacokinetic studies enabled rapid validation of in vitro-in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
130
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 66 publications
2
130
1
Order By: Relevance
“…The inhibitors were also assayed for inhibition of Janus kinase 2 (JAK2), as previous efforts had confirmed that JAK2/LRRK2 biochemical selectivity correlated with biochemical selectivity against the broader kinome. 22,23 The 3-and 5-amino-linked pyrazoles (2 and 3) demonstrated good JAK2/LRRK2 selectivity but appeared to have inferior potency for LRRK2 in our biochemical screen and cell-based LRRK2 autophosphorlyation assay when compared to the 4-linked aminopyrazoles (5−7). The poor JAK2 selectivity of compound 4 (2.7×) confirmed that a nitrogen lone pair (e.g., compound 2) or 3-/5-substituent was required to achieve good selectivity.…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 87%
“…The inhibitors were also assayed for inhibition of Janus kinase 2 (JAK2), as previous efforts had confirmed that JAK2/LRRK2 biochemical selectivity correlated with biochemical selectivity against the broader kinome. 22,23 The 3-and 5-amino-linked pyrazoles (2 and 3) demonstrated good JAK2/LRRK2 selectivity but appeared to have inferior potency for LRRK2 in our biochemical screen and cell-based LRRK2 autophosphorlyation assay when compared to the 4-linked aminopyrazoles (5−7). The poor JAK2 selectivity of compound 4 (2.7×) confirmed that a nitrogen lone pair (e.g., compound 2) or 3-/5-substituent was required to achieve good selectivity.…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 87%
“…Many kinase inhibitors will block LRRK2 activity, with CZC-25146 and LRRK2-IN1 having high specificity for LRRK2 [157][158][159]. Neither of these kinase inhibitors would be taken into clinical trials owing to their poor blood-brain barrier permeability [159], although more recent inhibitors may be have better distribution in the brain [160][161][162].…”
Section: Therapeutic Strategies For Lrrk2-associated Pdmentioning
confidence: 99%
“…The utility of these molecules is, however, largely confined to in vitro assays owing to poor pharmacokinetic qualities and a lack of brain penetration. More recently, two novel LRRK2 kinase inhibitors (GNE-7915 and GNE-0877) were disclosed and used to probe the safety and tolerability profile of LRRK2 kinase inhibition in rodents and nonhuman primates (Estrada et al, 2012;Fuji et al, 2015). However, despite possessing improved biodistribution properties, both compounds inhibit several off-target kinases, and GNE-0877 has been associated with dose limiting toxicity in rats (Fuji et al, 2015).…”
Section: Introductionmentioning
confidence: 99%